2007
DOI: 10.18475/cjos.v43i2.a6
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology of a Mangrove Forest in Jobos Bay, Puerto Rico

Abstract: ABSTRACT.-We studied gas exchange, leaf dimensions, litter production, leaf and litterfall chemistry, nutrient flux to the forest floor, retranslocation rates, and nutrient use efficiency of mangroves in Jobos Bay, Puerto Rico. The fringe forest had a salinity gradient from the ocean (35‰) to a salt flat (100‰) and a basin (about 80‰). Red (Rhizophora mangle), white (Laguncularia racemosa), and black (Avicennia germinans) mangroves were zoned along this gradient. Photosynthetic rates, stomatal conductance, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 29 publications
8
32
0
1
Order By: Relevance
“…The differences in Ca concentrations among the species studied confirm previous reports from tropical mangrove sites where these species occur together (Lacerda et al, 1986a;Medina et al, 2001;Barboza et al, 2006;Lugo et al, 2007). Calcium is an element capable of counteracting excess of Na ions in the interstitial water surrounding the roots by stabilizing membranes in root cells (Epstein, 1998) supporting the absorption of K, therefore, its presence in the soil solution may improve tolerance to high levels of salinity.…”
Section: Plantssupporting
confidence: 89%
See 1 more Smart Citation
“…The differences in Ca concentrations among the species studied confirm previous reports from tropical mangrove sites where these species occur together (Lacerda et al, 1986a;Medina et al, 2001;Barboza et al, 2006;Lugo et al, 2007). Calcium is an element capable of counteracting excess of Na ions in the interstitial water surrounding the roots by stabilizing membranes in root cells (Epstein, 1998) supporting the absorption of K, therefore, its presence in the soil solution may improve tolerance to high levels of salinity.…”
Section: Plantssupporting
confidence: 89%
“…The N and P concentrations are within the upper range of variation in mangroves elsewhere indicating that the sediments in these mangrove sites are quite fertile as suggested also by the soil analyses (Lacerda et al, 1985;Medina et al, 2001;Bernini et al, 2006;Lugo et al, 2007;Medina et al, 2010). Besides, the N/P molar ratios are all below 30 for the mangrove species, and slightly above 30 in the associated species, well below the values reported from P-limited mangroves in the Caribbean .…”
Section: Plantssupporting
confidence: 56%
“…It is interesting to note that the reflectance of the dwarf black mangrove was slightly lower than that for the poor condition black mangrove even though the difference was not significant (p > 0.01). In contrast to healthy black mangroves, dwarf black mangroves are typically found in sub-optimal conditions generally characterized by limited nutrients and freshwater [37][38][39][40]. Consequently, their height is generally not more than 1.5 m, as observed in our study site (Figure 1).…”
Section: Spectral Properties Of Mangrove Species and Conditionsmentioning
confidence: 49%
“…The dwarf red leaves were the most yellowish and consequently had the strongest reflectance in the red spectrum. Moreover, stressed mangrove leaves are generally smaller and thicker [31,37] and, thus, should have higher reflectance in the NIR region. In contrast, the reflectance of the stressed mangroves in our study was shown to be generally lower than the healthy mangroves in the NIR region.…”
Section: Spectral Properties Of Mangrove Species and Conditionsmentioning
confidence: 99%
“…Mangrove communities dominated by Rhizophora mangle, a salt excluder sensu (Scholander et al, 1962), and Laguncularia racemosa, a salt-secreting species with succulent leaves (Biebl and Kinzel, 1965;Tomlinson, 1986;Lugo et al, 2007;Sobrado, 2004), occur in the northern coast of South America in contiguous areas under similar climatic, edaphic, and salinity conditions. Both species are tolerant of high soil interstitial water salinity but differ in their tolerance to flooding, presence of salt-secreting glands, and the nature of compatible solutes accumulated in their leaves (Tomlinson, 1986;Medina et al, 2001).…”
Section: Introductionmentioning
confidence: 99%